Clinical Anatomy of the Shoulder : An Atlas - Bozkurt, Murat; Açar, Halil İbrahim (Springer International Publishing : Imprint: Springer, 2017)
This book provides detailed information on functional anatomy, physical examination, and clinical radiology of the shoulder with a view to enabling the clinician to identify the most suitable treatment approach to different shoulder joint pathologies. In addition, it describes the arthroscopic treatment techniques most frequently employed in patients with these conditions and presents numerous arthroscopic images detailing characteristic findings. The shoulder is widely regarded as the most complex joint in the human body, displaying the widest range of motion. Knowledge of normal and pathological anatomy, ability to perform a proper physical examination, and appropriate selection of imaging modalities and interpretation of imaging appearances, often in close collaboration with an imaging expert, are all vital for correct diagnosis and choice of treatment approach. Surgeons and trainees will find this richly illustrated book to be an excellent educational guide and an instructive source of stepwise guidance from clinical presentation to achievement of desired treatment outcomes.
Keywords: Medicine.; Human anatomy.; Radiology.; Orthopedics.; elektronické knihy; electronic books